MEIO AMBIENTE E JUSTIÇA AMBIENTAL: A EDUCAÇÃO AMBIENTAL COMO PRÁXIS SOCIAL - Pieper, Daniela da Silva; Santos, Tiago; Pimentel, Renan (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704142 This paper intends to discuss some elements of the fundamentals of environmental education(EE), the perspective of rapprochement between Freire's pedagogy and aspects of environmentaljustice, focusing on environmental conflicts immanent to the hegemonic social model. Seeking tounderstand the asymmetry of the appropriation of joint property attempts to indicate pedagogicalpossibilities since the emergence of ideas about the environment in the category view of EAcriticizes transforming and emancipatory. Therefore, it emphasizes the understanding of theenvironmental category, understood not as empirical abstraction, but in their historicaleffectiveness, in the expression of the relationships that they print the substance of space in theconstruction of all dialectic.